2011
DOI: 10.1111/j.1462-5822.2011.01612.x
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation by Salmonella enterica serovar Typhimurium colonizing solid tumours

Abstract: SummarySystemic administration of Salmonella enterica serovar Typhimurium to tumour bearing mice results in preferential colonization of the tumours and retardation of tumour growth. Although the bacteria are able to invade the tumour cells in vitro, in tumours they were never detected intracellularly. Ultrastructural analysis of Salmonella-colonized tumours revealed that the bacteria had formed biofilms. Interestingly, depletion of neutrophilic granulocytes drastically reduced biofilm formation. Obviously, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 38 publications
6
46
0
1
Order By: Relevance
“…stones (12,59), epithelial cells, and chicken intestinal tissues (63). In addition, S. Typhimurium has been shown to form biofilms as a defense against phagocytosis by host immune cells (64). Gunn and colleagues have demonstrated that S. Typhimurium is capable of producing biofilms in vitro in response to prolonged exposure to bile (e.g., 14 days), revealing that host factors can stimulate S. Typhimurium to initiate biofilm formation (30).…”
Section: Figmentioning
confidence: 99%
“…stones (12,59), epithelial cells, and chicken intestinal tissues (63). In addition, S. Typhimurium has been shown to form biofilms as a defense against phagocytosis by host immune cells (64). Gunn and colleagues have demonstrated that S. Typhimurium is capable of producing biofilms in vitro in response to prolonged exposure to bile (e.g., 14 days), revealing that host factors can stimulate S. Typhimurium to initiate biofilm formation (30).…”
Section: Figmentioning
confidence: 99%
“…Also, recent findings suggest that extracellular survival in spleen (a systemic site) is more desirable for Salmonella than cellular invasion. 42 This leads to many queries regarding the role of SPI2 in extracellular survival of Salmonella in these sites. So it can be speculated that SPI2-mediated functions may not be limited to intracellular survival and multiplication of Salmonella anymore, throwing light on the future platforms to work on the newly implicated roles of SPI2 in Salmonella pathogenesis.…”
Section: Future Aheadmentioning
confidence: 99%
“…Within a biofilm there is reduced diffusion, physiological changes due to reduced growth rates and production of enzymes which degrade antimicrobial substances 8 leading to increased resistance. Biofilms are a concern in the food industry as they can lead to illness, disease outbreaks with subsequent economic losses 12 . In the medical field, bacterial biofilms are worrying concerns because they can occur on the surfaces of medical devices and on tissue surfaces within compromised organs 13 .…”
mentioning
confidence: 99%